2020
DOI: 10.1101/2020.09.02.280107
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Kcns3Deficiency Disrupts Parvalbumin Neuron Physiology in Mouse Prefrontal Cortex: Implications for the pathophysiology of schizophrenia

Abstract: The unique fast spiking (FS) phenotype of cortical parvalbumin-positive (PV) neurons depends on multiple subtypes of voltage-gated potassium channels (Kv). PV neurons selectively express Kcns3, the gene encoding Kv9.3 subunits, suggesting that Kcns3 expression is critical for the FS phenotype. KCNS3 expression is lower in PV neurons in schizophrenia, but the effects of this alteration are unclear, because Kv9.3 subunit function is poorly understood. We therefore assessed the role of Kv9.3 subunits in PV neuron… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 80 publications
(131 reference statements)
0
1
0
Order By: Relevance
“…This analysis revealed that FSI in the App NL-G-F group at P60 had distinctive intrinsic properties since they clustered in a separate area of the plot compared to the App NL-G-F group at P30 and the WT groups at P30 and P60 (Fig Moreover, we found that the synaptic pathways were scarcely affected by maturation to these pathways were selected based on their involvement in gamma oscillations and FSI functionality as potential causes of early functional impairment during amyloid pathology progression. Kcnc1 [45][46][47], Kcns3 [48,49], Scn1a [50,51], Erbb4 [52][53][54][55],…”
Section: -Fast-spiking Interneuron Intrinsic Properties and Postsynap...mentioning
confidence: 99%
“…This analysis revealed that FSI in the App NL-G-F group at P60 had distinctive intrinsic properties since they clustered in a separate area of the plot compared to the App NL-G-F group at P30 and the WT groups at P30 and P60 (Fig Moreover, we found that the synaptic pathways were scarcely affected by maturation to these pathways were selected based on their involvement in gamma oscillations and FSI functionality as potential causes of early functional impairment during amyloid pathology progression. Kcnc1 [45][46][47], Kcns3 [48,49], Scn1a [50,51], Erbb4 [52][53][54][55],…”
Section: -Fast-spiking Interneuron Intrinsic Properties and Postsynap...mentioning
confidence: 99%